Percutaneus Nephorlithotomy Procedure for Realese Encrusted Double J Stent - Heryadi, Afrizal Tri; Laksono, Rizki Abri; Haryanto, Andry (Faculty of Medicine Universitas Sebelas Maret, 2023)
Installation of a DJ Stent is a procedure performed in the field of urology to prevent or relieve ureteral obstruction.Technological developments in the field of medicine have changed the approach to surgical intervention in cases of kidney stones (especially kidney stones with a stone burden > 2 cm), from open surgery to endoscopic surgery, one of them is by percutaneous nephrolithotomy (PCNL). We report the case of a man with a right double J (DJ) stent that was placed 5 months previously. The patient underwent anamnesis, physical examination, supporting examinations and was then treated with ureteroscopic lithotripsy and PCNL. Complete clearance of the stone can be performed and the DJ stent can be removed uninterruptedly from the percutaneous access. Encrusted stents are still a challenge in urology where endourology remains the best choice of treatment. The management of DJ stents should also be based on follow-up and prevention by taking into account predisposing factors to encrustation such as urinary tract infections, diabetes mellitus, chronic renal failure, history of urolithiasis, diet and malabsorption.